Behavior modification using the functional area specialization treatment protocol for children with autism - Aragon, Fermina F. (2008)
The Functional Area and Specialization Treatment (FAST) protocol for behavior modification was applied in this study. This protocol consists of gluten free casein free diet and virgin coconut oil. This study adopted the qualitative and quantitative research group design. The subjects were two groups, the control and experimental, consisted of 15 members each. The setting was at PRIME Center in Mandaue City, Cebu. Results showed that there was no significant difference in the pretest and the posttest scores of the children in the control group. It means that their behavior did not improve even after several months. However, the scores of the experimental group increased significantly, indicating improvement of the children's behavior. Based on this, the use of the FAST protocol is effective in modifying the behavior of children with autism in terms of speech, psychosocial interaction and aggressive behavior.